2016
DOI: 10.1007/s12035-016-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

A Neuroprotective Effect of the Glutamate Receptor Antagonist MK801 on Long-Term Cognitive and Behavioral Outcomes Secondary to Experimental Cerebral Malaria

Abstract: Cerebral malaria (CM) is a life-threatening complication of Plasmodium falciparum infection, which can result in long-term cognitive and behavioral deficits despite successful anti-malarial therapy. Due to the substantial social and economic burden of CM, the development of adjuvant therapies is a scientific goal of highest priority. Apart from vascular and immune responses, changes in glutamate system have been reported in CM pathogenesis suggesting a potential therapeutic target. Based on that, we hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 98 publications
2
22
0
Order By: Relevance
“…MK801 is a noncompetitive NMDA receptor antagonist that is thought to protect neurons in the brain against excitotoxicity induced by excessive glutamate activity [ 17 , 32 ]. MK801 was used as a NMDAR antagonist with the dose range from 0.2 to 1.0 (mg/kg) in previous studies [ 17 , 21 , 22 ].To explore the role of NMDARs in synaptic plasticity during ototoxicity, MK801 (0.2 mg/kg, i.p.) was used to rescue the gentamicin-induced damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MK801 is a noncompetitive NMDA receptor antagonist that is thought to protect neurons in the brain against excitotoxicity induced by excessive glutamate activity [ 17 , 32 ]. MK801 was used as a NMDAR antagonist with the dose range from 0.2 to 1.0 (mg/kg) in previous studies [ 17 , 21 , 22 ].To explore the role of NMDARs in synaptic plasticity during ototoxicity, MK801 (0.2 mg/kg, i.p.) was used to rescue the gentamicin-induced damage.…”
Section: Resultsmentioning
confidence: 99%
“…The second group of animals received daily i.p. injections of gentamicin (100 mg/kg in saline) and the NMDAR antagonist MK801 (0.2 mg/kg in saline, Sigma-Aldrich, USA) for 4 or 7 consecutive days [ 17 , 21 , 22 ]. The mice in the third group served as the control group and received daily injections of equivalent volumes of normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals infected with Plasmodium falciparum present a significant increase in anxiety and depression [ 4 , 36 ]. Several studies in experimental models of malaria also demonstrated anxiety and depression-like behavior alterations [ 37 39 ]. We also observed an increase in depression like-behavior in PbA-infected mice, while MSC treatment mitigated this behavioral alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced BDNF expression levels are associated with cognitive and behavioral disorders in neurological disorders, such as cerebral malaria [ 48 50 ]. Previous studies have showed reduced BDNF mRNA expression in the frontal cortex and the hippocampus [ 37 ] and in various brain regions, including the thalamus, hypothalamus, cerebellum, and brainstem in PbA-infected mice [ 51 ]. The downregulation of BDNF may be a point of no return for the neurological damages observed in cerebral malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to ensure that “CNS security” is made an appropriate priority in pathological cases, administering a glutamate receptor antagonist following a brain insult has, in many pre-clinical studies, indicated neuro-protective roles and improved prognoses ( Furukawa et al, 2003 ; de Miranda et al, 2016 ). However, the results of clinical trials have suggested that these drugs fail to improve long-term prognoses or reduce mortality after brain injury ( Davis et al, 1997 ; Lees, 1997 ; Maas et al, 2006 ).…”
Section: The Significance Of Potential Applications That Alter the Homentioning
confidence: 99%